Long-time behavior of a class of diffusive predator–prey systems with fear cost and protection zone. (November 2021) - Dong, Yaying; Li, Shanbing
Abstract: In the present paper, we study the long-time behavior of a class of diffusive predator–prey systems with fear cost and protection zone. The sufficient conditions for the extinction and persistence are established by using upper–lower solution method and comparison principle. The analytical results suggest that fear cost and protection zone have a significant impact on the dynamics.